Influence of the Ti-TiN-(Y,Ti,Al)N Nanolayer Coating Deposition Process Parameters on Cutting Tool Oxidative Wear during Steel Turning - Alexey Vereschaka; Catherine Sotova; Filipp Milovich; Anton Seleznev; Nikolay Sitnikov; Semen Shekhtman; Vladimir Pirogov; Natalia Baranova (Nanomaterials, 2023)
Ti-TiN-(Y,Ti,Al)N coatings with a three-layer architecture (adhesive Ti layer, transition TiN layer, and wear-resistant (Y,Ti,Al)N layer) were studied. When depositing coatings, three arc current values of the yttrium cathode were used: 65, 85, and 105 A. The yttrium contents in the coatings were 30, 47, and 63 at. %, respectively. When turning 1045 steel, a coating with 30 at. % yttrium showed better wear resistance compared to a commercial (Ti,Cr,Al)N coating. The coating with 63 at. % yttrium did not show an increase in wear resistance compared to the uncoated sample. Nanolayers with a high yttrium content are oxidized more actively compared to nanolayers with a high titanium content. Phase analysis shows partial retention of the initial phases (Y,Ti,Al)N and (Ti,Y,Al)N during the formation of the Y2O3 oxide phase in the outer layers of the coating and the presence of only the initial phases in the deep layers. Coating nanolayers with high contents of aluminum and yttrium lose their original structure to a greater extent during oxidation compared to layers without aluminum.